CRISPR-PCS Protocol for Chromosome Splitting and Splitting Event Detection in Saccharomyces cerevisiae - Yu Sasano; Satoshi Harashima (Bio-Protocol, 2017)
Chromosome engineering is an important technology with applications in basic biology and biotechnology. Chromosome splitting technology called PCS (PCR-mediated Chromosome Splitting) has already been developed as a fundamental chromosome engineering technology in the budding yeast. However, the splitting efficiency of PCS technology is not high enough to achieve multiple splitting at a time. This protocol describes a procedure for achieving simultaneous and multiple chromosome splits in the budding yeast Saccharomyces cerevisiae by a new technology called CRISPR-PCS. At least four independent sites in the genome can be split by one transformation. Total time and labor for obtaining a multiple split yeast strain is drastically reduced when compared with conventional PCS technology.